A comparison of P-300 study in subjective tinnitus with normal hearing patients and normal hearing adults - Yodthong, Napasswan; Yimtae, Kwanchanok; Thanawirattananit, Panida; Paholpak, Pattharee; Kasemsiri, Pornthep; Chayaopas, Nichtima (Asia-Pacific Journal of Science and Technology, 2025)
Tinnitus can occur in normal hearing subjects and interfere with daily life and well-being. The P300 auditory evoked potential is used to demonstrate the cortical pathway of the auditory system. This study aimed to compare P300 characteristics between tinnitus patients with normal hearing and healthy subjects and explore the relationship between P300 characteristics and tinnitus severity. This study included 18 tinnitus patients with normal hearing and 18 healthy subjects. Each group was divided into two age groups: 18-40 and 41-60. All subjects with a bilaterally normal pure tone threshold and type A tympanogram were included. The mini-cog screening test and a structured interview (M.I.N.I.) were used to evaluate cognitive impairment and psychiatric disorders. In healthy volunteers, a trend of longer latency and smaller amplitude of P300 was found as age increased. However, no significant difference between the two age groups was noted. When compared between tinnitus and healthy subjects, there was a significantly delayed latency of P300 in age groups of 18-40 years and 41-60 years (p<0.05), whereas P300 amplitude did not differ. We discovered a delayed result of P300 latency in subjective tinnitus in both two age groups (p=0.03 and p<0.01, respectively) and a relationship between tinnitus sufferers and altered P300 characters. Hence, P300 may be an objective measurement for diagnosing tinnitus patients.